Exploring Nausea and Vomiting: Pathophysiology, Mechanisms and Future Research Directions - K, Komal; A, Ashish; Parashar, Tarun; Singh, Neha (Indian Journal of Pharmacy Practice)
Nausea and Vomiting are among the major health burdens affecting nearly 90-95% of the worldwide population. Nausea and vomiting, commonly called emesis, are prevalent symptoms associated with various medical conditions and treatments. This review paper systematically examines the pathophysiology of emesis and the current landscape of antiemetic therapies, focusing on their mechanisms of action, efficacy, and adverse effects. The paper provides a comprehensive overview of the classes of antiemetic drugs consisting of antagonists of the dopamine, serotonin, and neurokinin-1 receptors among others. It offers insights into the comparative effectiveness of different antiemetic agents in diverse clinical settings, such as Nausea and Vomiting caused by Chemotherapy (CINV) and Nausea and Vomiting associated with Pregnancy (NVP). In conclusion, this review paper provides an extensive and current analysis of antiemetic therapies, offering clinicians and researchers valuable insights into the current state of antiemetic pharmacology.
Keywords: Nausea; Vomiting; Antiemetics; Herbal drugs